Gibberellin: inhibitor of an inhibitor of...? - Harberd, N; King, K; Carol, P; Cowling, R; Peng, J; Richards, D (1998)
Gibberellin is an endogenous plant growth regulator. Here, we describe our present understanding of how gibberellin regulates plant growth, using recent results gained from studies of gibberellin-signalling mutants of Arabidopsis. These results show that a signalling pathway represses plant growth and that gibberellin releases this repression. In consequence, the well-known growth-promoting properties of gibberellin are due to its activity as an "inhibitor of an inhibitor" [Brian Pw. Sym Soc. Exp Bio 1957; 11:166-182 (Ref. 1)] of plant growth.